Hubungan tingkat pengetahuan tentang rokok dengan perilaku merokok pada remaja di SMKN Pagelaran Utara Pringsewu Lampung - Atmasari, Yeti; Sanjaya, Riona; Fauziah, Nur Alfi (Utan Kayu Publishing, 2020)
Smoking behavior is related to public health. Smoking is a behavior that has a tendency to begin during adolescence. Factors that are closely related to smoking behavior in adolescents are knowledge. The purpose of this study was to determine the relationship between the level of knowledge about cigarettes and smoking behavior in adolescents in North State Vocational High Schools in 2019. The design used in this research is quantitative research with a cross sectional approach. The population in this study were male students at North Pagelaran Vocational High School 2018/2019 in 98 students. The sampling technique used in this study is total sampling. The sample in this study were 98 respondents. The results of univariate analysis revealed that respondents who had good knowledge were 62 respondents (63.3 percent) and respondents who were light smokers were 46 respondents (46.9 percent). There is a relationship between the level of knowledge about smoking in smoking behavior in adolescents in North State Vocational High School Year 2019 with a p-value of 0,001. For adolescents to start doing healthy behaviors such as exercising regularly as an effort to stop smoking or avoid smoking.Â Abstrak:Â Perilaku merokok berkaitan dengan kesehatan masyarakat.Merokok merupakan perilaku yang memiliki kecendrungan dimulai saat masa remaja. Faktor yang berkaitan erat dengan perilaku merokok pada remaja adalah pengetahuan. Tujuan penelitian ini untuk mengetahui hubungan tingkat pengetahuan tentang rokok dengan perilaku merokok pada remaja di SMKN Pagelaran Utara Tahun 2019. Desain yang digunakan dalam penelitan ini penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah siswa laki-laki di SMKN Pagelaran Utara Tahun ajaran 2018/2019 sebanyak 98 siswa. Tekhnik sampling yang digunakan dalam penelitian ini adalah Total sampling. Sampel dalam penelitian ini sebanyak 98 responden. Hasil Analisa univariat diketahui responden yang memiliki pengetahuan baik sebanyak 62 responden (63,3 persen) dan responden yang merupakan perokok ringan sebanyak 46 responden (46,9 persen). Ada hubunganÂ antara tingkat pengetahuan tentang rokok perilaku merokok pada remaja di SMKN Pagelaran Utara Tahun 2019 dengan p-value sebesar 0,001. Bagi remaja untuk memulai melakukan perilaku hidup sehat seperti melakukan olah raga secara teratur sebgai upaya berhenti merokok maupun menghindari merokok.